Effect of Self-Esteem on Customer Citizenship Behaviours among International University Branch Campus Students - Tan, VieMing; Quoquab, Farzana; Ahmad, Fauziah Sh.; Mohammad, Jihad (International Review of Management and Marketing, 2016)
Major universities have expanded overseas by establishing international branch campuses (IBCs) since the mid-1990s. Many campuses have only been in operation for a decade. Hence, engagement of students is valuable to assist in the design, development, and review of transnational programmes. Customer citizenship behaviours (CCBs) of individual student such as self-willingness to provide constructive feedback to university and help other students are valuable to improve university operation efficiency. Most CCB antecedents have been found based on social exchange theory by believing that customer reciprocates positive behaviour for rewarding those who benefit them. However, Rosenberg (1965) uses self-consistency theory to argue that self-esteem influences behaviour due to self-consistency motive. This research argues that it is still not clear whether the self-esteem leads to pro-social responses among students. Hence, this research aims to examine effect of self-esteem on CCB among IBC students. A sample of 400 students from four IBCs in Malaysia was collected via survey questionnaire. The collected data were analysed using SPSS and PLS3 which empirically support that self-esteem has positive effect on all three CCB dimensions. Thus, CCBs of IBC students are explained by self-consistency theory in which students perform CCB with the motive of maintaining self-image. Keywords: International university branch campuses; customer citizenship behaviour; self-esteem; self-consistency theory. JEL Classifications: I23, M16, M31